Corruption and Economic Growth in ASEAN Member Countries - Anisah Alfada (Institute for Economic and Social Research, 2019)
This study examines the effect of corruption on economic growth and determines the corruption threshold in nine ASEAN member countries in 1999–2016. This study assesses whether the effect of corruption is growth-enhancing or growth-deteriorating in different corruption threhsolds using a sample-splitting and threshold model. In contrast to the existing literature, this study does not group countries based on income level and therefore can reveal the corruption level of a country relative to a corruption threshold. The estimation results show that the adverse effect of corruption on economic growth is stronger for countries with corruption levels above the second threshold of 80.